The Effect of Extraction Methods of White Saffron (Curcuma mangga Val.) on The Antioxidant Activity - Dwiyati Pujimulyani; Agung Wazyka; Sri Anggrahini; Umar Santoso (agriTECH, 2006)
A study on the effect of white saffron to distilled water ratio on the antioxidant activity ofwhite saffron extract has been conducted. White saffron rhizome was blanched in the 0.5% citric acid solution at 100Cfor 5 min, and grated. The grated rhizome was extracted with distilled water at the ratio of 1: 1, 1:2, 1:3 and 1:4, respectively. The antioxidant activity of white saffron extract was assayed with Ferry Thyo Cyanate (FTC) and Thio Barbituric Acid (TBA) methods and compared with standard of BHA. The antioxidant activity ofwhite saffron extract expressed as % .inhibition, and the control (without added white saffron extract) was considered as having 0 % activity. Higher decrease of antioxidant activity was found with higher ratio of white saffi-on to distilled water. The highest antioxidant activity of white saffron extract (MC method 20.17% and TBA method 32.15%) was found in 1:1 ratio.